A Study of the Insurance Perspective in Uthamapalayam Taluk - Hasanbanu, S.; Nagajothi, P. S. (Indian Journal of Marketing, 2007)
Most of the Asian countries with the exception of Japan, South Korea and Taiwan have a low insurance penetration as compared to developed enlightened countries. India is an agricultural country. The earnings of many of our people are not enough for their livelihood. So they are unable to make investments in savings. They give priority to their food, medical attention and education. They think of savings for the future. The main aim of the most of the investors is to gain tax relief. So, many people lack knowledge of the necessity of insurance. The Life Insurance industry has come a long way since independence, and Indian consumers till recently had been dealing with only one life insurance player - the Life Insurance Corporation (LIC) in the public sector. After the liberalization of the insurance sector more than a dozen companies have entered the business. These new insurance companies started operating from metros and urban areas. As a result the urban population got more attention and it led to good insurance penetration in urban areas as compared to rural markets. Hence the rural people don’t have a chance to learn about insurance. The LIC, in fact, was the number one Government-owned insurance company that had not only made substantial profits, but also earned the trust of people.The present study is an attempt to learn the perspective of insurance in Uthamapalayam taluk, the attitude of policy holders towards the performance of the LIC and their level of investments.